PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS AUGMENTED REALITY (AR) TERINTEGRASI ETNOMATEMATIKA MINANGKABAU UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Asri Ramadhani; Camelia Susi Handayani; sukriadi hasibuan (Jurnal Dharma PGSD, 2026)
Abstract : Critical thinking skills are crucial competencies that elementary school students must possess in mathematics learning. However, the mathematics learning process continues to face various challenges due to the abstract nature of the materials and the use of learning media that lack engagement and contextual relevance. A viable alternative to address these issues is the use of Augmented Reality (AR)-based learning media integrated with Minangkabau ethnomathematics. This study aims to develop AR-based mathematics learning media integrated with Minangkabau ethnomathematics to enhance the critical thinking skills of elementary school students. This research employed a Research and Development (R&D) method using the ADDIE model, which encompasses the analysis, design, development, implementation, and evaluation stages. The subjects of the study consisted of 30 elementary school students. Data were collected through validation questionnaires, practicality questionnaires, and critical thinking skill tests. The results demonstrated that the developed media achieved a validity rate of 93.2% (highly valid category), a practicality rate of 91.4% (highly practical category), and an effectiveness rate of 89.7% (highly effective category). Furthermore, the students' average critical thinking score improved significantly from 61.8 at the initial stage to 84.6 following the use of the media. The research findings indicate that integrating Augmented Reality (AR) technology with Minangkabau ethnomathematics can create a more interactive, contextual, and meaningful mathematics learning experience, thereby effectively enhancing the critical thinking skills of elementary school students.